Comparison of percutaneous endoscopic lumbar discectomy versus open lumbar microdiscectomy for lumbar disc herniation: A meta-analysis. (July 2016) - Ruan, Wenfeng; Feng, Fan; Liu, Zhengye; Xie, Jiangtao; Cai, Lin; Ping, Ansong
Abstract: Purpose: The purpose of the study is to perform a systematic review and meta-analysis to evaluate the clinical results of percutaneous endoscopic lumbar discectomy (PELD) and open lumbar microdiscectomy (OLM) for the treatment of lumbar disc herniation (LDH). Methods: Randomized controlled trials or non-randomized controlled trials published from the time when databases were built to March 2016 that compared the clinical effectiveness of PELD and OLM surgical approaches for the treatment of LDH were acquired by a comprehensive search in four electronic databases (PubMed, EMBASE, Web of Science and Cochrane library). A total of 7 studies (1389 patients) were included in this systematic review and meta-analysis. Pooled mean differences (MD) and odds ratios (OR) and with 95% CIs were calculated for the outcomes. Result: The results showed that there were no statistically between the PELD group and OLM group in terms of preoperative VAS-BP score (WMD = 0.03; 95% CI: −0.99 to 1.05; P = 0.95), postoperative VAS-BP score (WMD = −0.56; 95% CI: −1.43 to 0.31; P = 0.21), postoperative ODI (WMD = −0.98; 95% CI: −4.96 to 3.00; P = 0.63), complication rate (OR = 1.79; 95% CI: 0.95 to 3.37; P = 0.07) or reoperation rate (OR = 1.44; 95% CI: 0.94 to 2.20; P = 0.09). PELD group was associated with shorter operation time (WMD = −12.83; 95% CI: −24.79 to −0.87; P = 0.04) and hospital stay (WMD = −5.49; 95% CI: −8.63 to −2.35; P = 0.0006). Conclusion: The existing evidence indicate that no superiority exists between the two surgical approaches for the treatment of LDH in terms of functional outcome, complication rate and reoperation rate, in spite of that PELD surgical group can achieve shorter operation time and hospital stay than OLM surgical group. Highlights: First meta-analysis to evaluate the outcomes of PELD and OLM for the treatment of LDH. A total of 1389 patients were included in this systematic review and meta-analysis. This study allows the surgeon to understand the difference between the two approaches.